Nilai Agilitas pada Atlit Sepakbola di DKI Jakarta - Regie Santoso; Tirza Z Tamin (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Agility score is important in setting the rehabilitation’s goal of injured athlete. More agility requirement needs more rehabilitation effort. The aim of this study is to measure the agility score of junior soccer athletes in Jakarta and compare the agility score based on athlete’s playing positions. Methods: Agility score of 65 junior athletes measured using T-Agility test. Subjects categorized based on playing positions which are defender, midfielder and forward. Mean agility score of each group was then compared. Data analyzed using descriptive analysis and one-way annova. Results: The mean agility score is 10.89 ± 0.47 seconds. The mean agility score in defender is 11.02 ± 0.51, midfielder 10.79 ± 0.41 and forward 10.73 ± 0.47. No significance statistical difference between the three groups (p=0,70). Conclusion: Agility score of junior soccer athletes in Jakarta using the T-Agility test is 10.89 ± 0.47 seconds and may illustrate the risk of sport injury. The forward soccer player has higher agility score compared to the midfielder and defender.